A Genomewide Association Study of Nicotine and Alcohol Dependence in Australian and Dutch Populations - Lind, Penelope A; Macgregor, Stuart; Vink, Jacqueline M; Pergadia, Michele L; Hansell, Narelle K; de Moor, Marleen H. M; Smit, August B; Hottenga, Jouke-Jan; Richter, Melinda M; Heath, Andrew C; Martin, Nicholas G; Willemsen, Gonneke; et al. (Twin research and human genetics, 2010)
Persistent tobacco use and excessive alcohol consumption are major public health concerns worldwide. Both alcohol and nicotine dependence (AD, ND) are genetically influenced complex disorders that exhibit a high degree of comorbidity. To identify gene variants contributing to one or both of these addictions, we first conducted a pooling-based genomewide association study (GWAS) in an Australian population, using Illumina Infinium 1M arrays. Allele frequency differences were compared between pooled DNA from case and control groups for: (1) AD, 1224 cases and 1162 controls; (2) ND, 1273 cases and 1113 controls; and (3) comorbid AD and ND, 599 cases and 488 controls. Secondly, we carried out a GWAS in independent samples from the Netherlands for AD and for ND. Thirdly, we performed a meta-analysis of the 10,000 most significant AD- and ND-related SNPs from the Australian and Dutch samples.